Characteristics of tickborne infections in the underexplored areas of the Trans-Baikal Territory - E. K. Lagunova; M. A. Khasnatinov; G. A. Danchinova (Acta Biomedica Scientifica, 2024)
Background. Infections transmitted to humans by the bites of ixodid ticks remain an urgent public health problem. In this work we explored the natural foci of tickborne infections located in the valley of the Chikoy River, which is a part of the buffer zone of the Baikal natural territory.The aim. To characterize the modern diversity and prevalence of tick-borne pathogens in the ecosystems of the valley of the Chikoy River (Trans-Baikal Territory, Russian Federation).Materials and methods. Thirteen sampling sites were located in typical biotopes throughout the Chikoy valley. In total 48  adult Ixodes persulcatus ticks, 1  female Haemaphysalis concinna tick and 38 specimens of small mammals were studied. All samples were tested for infection with seven tick-borne pathogens using multiplex real-time PCR.Results. No pathogens were detected in the H. concinna specimen. No R. sibirica and R. heilongjiangensis were detected both in ticks and in rodents. Among I. persulcatus, tick-borne encephalitis virus (TBEV), and the prevalence of Borrelia burgdorferi s. l. comprised 39.5 %, A. phagocytophilum – 16.7 %, B. miyamotoi – 8.3 % and Ehrlichia sp. – 2.1 %. Among infected ticks 6.2 % were co-infected with B. burgdorferi s. l. and A. phagocytophilum. Four rodent hosts of ticks and infections were identified: Myodes rufocanus (44.7  %), Apodemus peninsulae (39  %), Microtus oeconomus (13.2  %) and M.  rutilus (2.6  %). Mean prevalence of B.  burgdorferi  s.  l. in  rodents comprised 39.5 %, B. miyamotoi – 28.9 %, Ehrlichia sp. – 21.1 % and A. phagocytophilum – 18.4 %. TBEV was detected in 5.3 % of rodents.Conclusion. At least five tick-borne pathogens circulate in the Chikoi River valley, i. e. TBEV, B. burgdorferi sensu lato, A. phagocytophilum, B. miyamotoi and Ehrlichia sp. The wide spread of I. persulcatus and abundance of competent rodent hosts of infections and ticks indicates that natural foci of tick-borne diseases are widely distributed in the Chikoi River valley.